Pore Types and Characteristics of Ultra-Deep Shale of the Lower Paleozoic Wufeng-Longmaxi Formations in the Eastern Sichuan Basin - Ruolong Chi; Ping Gao; Yidong Cai; Ruobing Liu; Jinghan Du; Qin Zhou (Energies, 2023)
Recently, shale gas exploration of the Wufeng-Longmaxi formations (WF-LMX) in the Sichuan Basin has gradually stepped into deep to ultra-deep layers, but the pore types and characteristics of ultra-deep shale still remain unclear. In this study, the WF-LMX ultra-deep organic-rich shale samples in the Eastern Sichuan Basin were collected, and the types and development characteristics of shale pores were investigated by using high-resolution scanning electron microscopy (SEM). Our results showed that the pores of the WF-LMX ultra-deep shale reservoirs mainly included organic pores, mineral matrix pores (interparticle pores and intraparticle pores), and micro-fractures, which were dominated by organic pores, displaying oval, slit, and irregular shapes and a diameter of mainly 5–45 nm. Organic pores were poorly developed in primary organic matter (e.g., graptolite and radiolarian), while they were well developed in solid bitumen, being the most important nanopore type in shale. The pore development of ultra-deep shale was mainly controlled by the contents of organic matter and brittle minerals. Higher contents of organic matter and quartz are conducive to the development and preservation of organic pores, which are also favorable for ultra-deep shale gas exploration.